Description of technical characteristics for EEG equipment and their comparison for electroencephalographs available in Russia - А. А. Ivanov (Эпилепсия и пароксизмальные состояния)
The current study was aimed at providing a detailed description of the major technical characteristics for electroencephalographic (EEG) equipment and their impact on quality of the recorded signal. Understanding the importance of the recording equipmenttechnical parameters will help medical professionals make the right choice while purchasing new equipment as well as correctly set the necessary recording parameters to ensure the maximum possible quality of EEG signal. In addition, the technical characteristics for EEG equipment available in Russia were compared. Such a comparison became possible after the full package of documents for registered medical equipment including data on relevant technical parameters began to be published at the Roszdravnadzor website since 2023.